Fábrica de software-fordista ou pós-fordista, qual direção? : um estudo de caso sob a ótica do empresário empregador - Mello, André Corrêa de (2007)
This work analyzes the national software industl)', particularly software for export and software factories, focusing on the strategies and challenges of the national infonnation technology businesses acting in this sector. The major factors influencing the success or failure of national infonnation technology businesses that invest in the software factol)' segment were put into perspective considering concepts of taylorism, fordism, flexiblization of labor, current labor law, competitiveness of the software market, the maturity of management processes and social responsiblity ofbusinesses.